Phylogeography of the Black Kite (Milvus migrans) in Punjab Wetlands: Assessing genetic connectivity and lineage admixture at a migratory crossroads - Muhammad Zeshan Haider; Gulnaz Afzal; Hafiz Ishfaq Ahmad; Javed Hussain; Iram Qadeer; Shakeel Ahmed; Laila A. AL-Essa; Nisar Ahmad Koka; Aiman A. Alsaegh; Yehia Hazzazi (PLoS ONE, 2026)
The Milvus genus presents a taxonomic challenge due to the complex delineation of its evolutionary units. Research on the potentially divergent mitochondrial lineages within Milvus migrans in Pakistan remains sparse, leaving the regional phylogeny largely uncharacterized. This study utilized partial COI gene sequences to evaluate genetic relationships and identify the presence of divergent lineages within Pakistan’s M. migrans populations. Samples collected from three Punjab wetlands (Chashma Barrage, Taunsa Barrage, and Patisar Lake) were integrated with global GenBank reference sequences to evaluate maternal diversity and reconstruct demographic histories. Maternal genetic distances among regional conspecifics were remarkably low, ranging from 0.00% to 1.00%. However, comparisons across more divergent mitochondrial lineages revealed distances reaching 2.00%, particularly between West African and European isolates; notably, these intraspecific values remained distinctly lower than the significant divergence observed with outgroup taxa. Neutrality tests indicated signatures consistent with population expansion or purifying selection. A hierarchical AMOVA confirmed strong continental-scale genetic structuring (65.39% of total variation) contrasting with high gene flow within Punjab’s panmictic local populations. Principal Coordinates Analysis (PCoA) revealed lineage-driven clustering, supporting a homogeneous admixture of three mitochondrial lineages within the Indus Flyway. These results collectively reveal a significant intersection of divergent lineages within Pakistan’s M. migrans populations, highlighting the Punjab region as a critical zone of genetic admixture. While the data indicate high maternal connectivity and extensive haplotype sharing with distant global lineages, they also hint at complex evolutionary histories. These findings underscore the ecological importance of Punjab wetlands as a migratory hub, though the hypothesis of cryptic diversity remains tentative and requires future validation via multi-locus nuclear genomic markers.